Peran Pariwisata Berbasis Industri dalam Pengembangan Bisnis di Indonesia - Marlina, Leni; Hidayati, Nurul (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
Tourism has many origins regarding the tourist spots, as well as the people. Society basically plays an important role in the realization of a tourist spot. There are local people who act as owners and managers and run their business in tourist areas, as well as people as visitors from tourist attractions. In tourism there is a tourism industry in it which is one of the largest and fastest growing industries in the world. The tourism industry is one of the largest and fastest growing industries in the world. The tourism industry is very different from other industries, such as the clothing industry and the agricultural industry, the hospitality industry is more likely to operate in providing services. Tourism is part of business development in Indonesia, starting from hotels in it, modern tourism, marine tourism and other tours, which play a role in the progress and development of business in Indonesia. Increasing population growth, coupled with increasing economic needs, makes people develop the creativity of their people to develop businesses based on the tourism industry.